Analysis of Risk-Based Bank Ratings in Banking Companies before and After Merger: Case Study Indonesian Banking Industries - Selviana, Salsa (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
The difficulties experienced by banks in Indonesia appear to be very prolonged, even though Bank Indonesia has carried out its duties as lender of last resort namely the inherent function of protecting the bank in the event of liquidity difficulties. This banking crisis ultimately led to the liquidation of many banks and mergers. The purpose of this study is to analyze the health of banks in banks that carried out merger actions from 2015 to 2019 and banks listed on the IDX. Research was analyzed using the RBBR method (Risk Based Bank Rating). The method in this study was conducted based on credit risk and liquidity risk as measured using the NPL ratio (Non Performing Loan) and LDR ratio (Loan Deposit Ratio). GCG factors are measured by GCG composite ratings published by banks, factors earnings calculated using the ROA ratio (Return on Asset) and NIM (Net Interest Margin). Factor Capital calculated by CAR ratio (Capital Adequacy Ratio). The results of the RBBR analysis show that in general, almost all assessment factors have decreased, except for factors capital just.